The Impact of Visfatin Level Against Blood Pressure Among Pregnant Women - Rinawati, Luh Putu; Yanty, Jannah Sofy; Rakhmawati, Aprilia; Bekti, Heri Setiyo (JURNAL INFO KESEHATAN, 2023)
Visfatin, a protein with a molecular weight of 52 kDa, has been demonstrated to increase in the bloodstream. Visfatin has been shown in several studies to be a potential marker of preeclampsia. The objective of this study was to describe visfatin levels in pregnant women in Gianyar, Bali. An observational design was employed in this study to describe visfatin levels in 41 pregnant women in Ubud, Gianyar regency, Bali. Visfatin levels were determined by examining EDTA blood samples using the Elisa method and reading them at 450 nm on a microplate reader. The average value of visfatin levels was 6.49 ng/ml, according to the results. The average visfatin level based on hypertension blood pressure respondents was 3.74 ng/ml. This result was lower than that of normal blood pressure respondents.  This study's decrease in visfatin levels may have a smaller effect on physiological insulin resistance. The average visfatin level in second trimester respondents was 7.9 ng/ml higher than 5.7 ng/ml in third trimester respondents. The increase in visfatin levels suggests that visfatin may play a role in the pathogenesis of preeclampsia. Visfatin has the potential to be used as a biomarker to detect preeclampsia earlier, allowing pregnant women with preeclampsia to receive appropriate treatment.